Plasmonic targeting of cancer cells in a three-dimensional natural hydrogel. Issue 37 (17th September 2018) - Minai, Limor; Hamra, Matan; Yelin, Dvir
Abstract : Plasmonic eradication of malignant and normal cells co-cultured on a natural hydrogel showed dominant rapid photothermal damage mechanisms. Abstract : Using specifically designed gold nanoparticles and local laser irradiation, individual cells and small cell clusters could be targeted on a microscopic scale with minimal toxicity to nearby tissue. To date, most scientific studies and technological demonstrations of this approach were conducted on two-dimensional cultures, while most feasibility tests and preclinical trials were conducted using animal models. For bridging the gap between two-dimensional cell cultures and animal experiments, we propose and demonstrate the use of a natural hydrogel for studying the effect of intense, ultrashort laser pulses on a gold nanoparticle targeted tissue. Using illumination parameters comparable to those used with two-dimensional cultures, we show the complete eradication of multilayered cell colonies comprising normal fibroblasts and malignant epithelial cells co-cultured on a hydrogel scaffold. By evaluating the extent of cell damage for various pulse durations at off-resonance irradiation, we find that the observed damage mechanism was dominated by rapid thermal transitions around the gold nanospheres, rather than by photoionization. The work provides a new tool for understanding the complex pulse–particle–tissue interactions and demonstrates the important role of nanoparticle mediated cavitation bubbles in a thick, multilayered tissue.